ROMANTISME DALAM LAGU RANDAI RANTAU KUANTAN - Bisea Basti; Elmustian Elmustian; Syafrial Syafrial (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The purpose of this study is to describe the content of meaning contained in the lyrics of the song Randai Rantau Kuantan. This study uses a qualitative research design with descriptive research type. The technique of collecting data for this research is downloading, listening and taking notes. The method used in this research is descriptive qualitative. The data analysis technique for this research is content analysis as follows: (1) Downloading videos from YouTube (2) Listening to song lyrics carefully (3) Translating into written form (4) Finding romance in song lyrics (5) Analyzing data according to theory (6) Summarizing data. The research data source is from the YouTube fada music record and the latest viral 2019. The results of this study indicate that the songs randai rantau kuantan Olang Binti and Sayang Den Du belong to Romanticism in the form of natural, emotional and romantic images.Keywords: Romanticism, Randai rantau kuantan, Literature.